2023
DOI: 10.3390/ijms24054319
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Coagulopathy and Inflammatory Response in SARS-CoV-2 Infection among Type 2 Diabetic Patients

Abstract: Chronic inflammation and endothelium dysfunction are present in diabetic patients. COVID-19 has a high mortality rate in association with diabetes, partially due to the development of thromboembolic events in the context of coronavirus infection. The purpose of this review is to present the most important underlying pathomechanisms in the development of COVID-19-related coagulopathy in diabetic patients. The methodology consisted of data collection and synthesis from the recent scientific literature by accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that platelet count is important for the development of thrombotic complications in patients with SARS-CoV-2 infection [39]. In this study, we compared PD patients divided into two groups based on the inclusion of calcitriol in therapy and found no significant difference between the studied groups in terms of platelet count.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that platelet count is important for the development of thrombotic complications in patients with SARS-CoV-2 infection [39]. In this study, we compared PD patients divided into two groups based on the inclusion of calcitriol in therapy and found no significant difference between the studied groups in terms of platelet count.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, IL-6 contributes to the hypercoagulability status together with TNF-α and IL-1, a phenomenon which, if accompanied by severe inflammatory syndrome, leads to disseminated intravascular coagulation [10,14]. In the SARS-CoV2 infection, there has been an "infection-induced coagulopathy" phenomenon, resulting from hyperactivation of endothelial cells (due to the increased amount of IL-6) and increased release of tissue factor [21].…”
Section: Discussionmentioning
confidence: 99%
“…To elaborate, in addition to baseline endothelial dysfunction associated with HTN [ 17 ] and diabetes [ 18 ], COVID-19 induces significant cytokine release, infection-associated endothelial dysfunction, profound inflammation, and an overall hypercoagulable state. These factors may have predisposed these patients to develop ischemic strokes [ 19 ]. Another severe manifestation was an ICH that presented in a patient with both DM and HTN [ 20 ].…”
Section: Discussionmentioning
confidence: 99%